Exact numerical algorithms for linear stochastic wave equation and stochastic Klein-Gordon equation - Gerhard Winkler; Sergej M. Prigarin; Andreas Martin (Ludwig-Maximilians-Universität München, Sonderforschungsbereich 386 - Statistische Analyse diskreter Strukturen, 2003)
On the basis of integral representations we propose numerical methods to solve the stochastic wave equation and the stochastic Klein-Gordon equation. The algorithms are exact in a probabilistic sense.
urn:nbn:de:bvb:19-epub-1706-6
Keywords: 519